EFEKTIVITAS BIMBINGAN KELOMPOK DENGAN TEKNIK MODELING UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Puput Meylasari; Agus Wibowo; Hadi Pranoto (Counseling Milenial (CM), 2024)
The research this study are to "know the effectiveness of group guidance with modeling techniques to increase the learning motivation of orphaned students at Bakti Darma Punggur Junior High School" and to test the effectiveness of group guidance services using the modeling technique that the researchers developed. The results of the research carried out are: 1) The effectiveness of group guidance services with modeling techniques for orphaned students at Bakti Darma Punggur Junior High School in the 2023/2024 academic year, 2) Increased learning motivation for orphaned students of Bakti Darma Punggur Junior High School who managed to get results with the category " very high”.